Strategies to Succeed with Inclusion in a Diverse Learning Environment - May Olaug Horverak (IAFOR Journal of Education, 2023)
Even though inclusion is a strong principle in the Norwegian educational system, there are challenges when it comes to creating inclusive learning environments. This study investigates the following: a) What challenges are there in the learning environment in primary school from a teacher’s perspective, and b) what strategies do teachers employ to address these challenges and create an inclusive learning environment? The framework for data collection in this study has been a project called SAMM: A Systematic approach to work with mastery, participation, and motivation, where a method based on health promotion theory and self-determination theory has been developed and applied. Ten teachers were interviewed, after applying a five-step method where the students identify what is important for them, success factors and obstacles, and make plans regarding what to focus on and what to do. The teachers interviewed applied the five-step method with focus on life mastery, subjects, or the social environment. A summative, traditional content analysis has been conducted, based on categories identified in a preliminary study, which investigates challenges and solutions in a diverse learning environment from a student’s perspective. The three main categories in the analysis were relational challenges, structural challenges, and individual challenges. The study concludes that it is important to work systematically and over time to create an inclusive learning environment. In line with different studies that have investigated interventions for children with behavioural problems in middle school, it is also recommended to facilitate self-regulation and choice-making to create an inclusive learning environment.